Dante's Epic Journeys - Thompson, David (Johns Hopkins University Press, 2019)
Originally published in 1974. This book on comparative literature represents the first extended attempt to relate Dante's major allegorical mode to classical and medieval interpretations of epic poetry rather than to patristic biblical exegesis. Dante's Epic Journeys is also the first comprehensive explanation of Dante's enigmatic Ulysses. Thompson strives to shed new light not only on Dante's allegory-and thus upon the whole troubled question of exactly what an allegory was thought to be-but also on the intricate relationship between poet and poem and between Dante's spiritual journeys and his written representation of those itineraries.